Assessing the societal benefits of mahseer (Tor spp.) fishes to strengthen the basis for their conservation. Issue 10 (18th August 2021) - Everard, Mark; Pinder, Adrian C.; Claussen, Julie E.; Orr, Stuart
Abstract: Mahseer ( Tor  spp., Cyprinidae) are iconic, large‐bodied, migratory freshwater fishes of Asian rivers. Long valued as a food source and serving other societal roles, these fishes are severely threatened by a broad range of interacting and escalating human impacts, including dam construction, water pollution, over‐exploitation, and habitat destruction. Mahseer fishes are therefore beneficial to people, both directly and as indicators of ecosystem functionality and the associated ecosystem service benefits provided by the rivers that they inhabit. A literature review demonstrated that wild mahseer populations have a direct role in 11 of the 36 ecosystem services assessed and are indicative of a further 18 ecosystem services provided by the habitats that support them. Recognition of this range of ecosystem service benefits is helpful in describing to non‐specialist public and policy‐making communities the diversity of values provided by mahseer fishes and their supporting habitats, and hence the importance of their conservation. Assessment of the broad range of ecosystem services to which mahseer contribute is an approach that could usefully be applied to promote the benefits of conserving other 'umbrella' taxa and the habitats that support them.